Disaster Management by Security Agencies in Nepal - Paudel, Narendra Raj (Journal of APF Command and Staff College, 2023)
As per the MOHA report (2021), disaster has been claiming life and property of people. MOHA has its plan to tackle the Disaster because of the fact that Nepal is a disaster-prone country. The categories of disaster as per MOHA report, 25 types of disasters have been happing in Nepal and causing loss of life and property of people. In this context, this article aims to find out the situation of disasters in the country as whole and province-wise scenarios of disaster cases; examine the sufficiency of security personnel to implement the disaster policy mandate given by the government of Nepal and elucidate the required coordination for preparedness, responses and rescue operations that have to carry out by the security agencies in support of three tiers of governments. For this purpose, secondary data from the MOHA web pages were retrieved to analyze the interrelationship of each disaster. Likewise, policies related to preparedness and response in general, especially to security agencies were reviewed. Key informants (KI) interview was taken to consolidate findings from the secondary data. Koshi Province is in the top position of the disaster cases whereas Sudurpaschhim Province is at the lowest position out of 26148 disaster cases from 2011 to 2021 June. Despite the deficiency of human resources in the security agencies and the lack of proper coordination made by the three tiers of government, security agencies accomplish the roles of preparedness, response and rescue operation more than their capacity to save life and property of people. The study concludes that disaster management is not the government's priority whatever its claim in government policy documents due to lack of appropriate coordination with the security agency and insufficient security personnel. The coordination and ensuring of required security personnel is the responsibility of the government when it concerns disaster management by the security agencies in Nepal.